In Vivo Study of Telang Cream on Interleukin (IL)-6, Epidermal Growth Factor (EGF), and Wound Reepithelialization - Nike Pratiwi; Nurmayani Irwandi; Restu Syamsul Hadi; Nabila Pyrenina Thamrin; Ndaru Andri Damayanti; Juniarti Juniarti; Nunung Ainur Rahmah (Sekolah Vokasi Universitas Gadjah Mada, 2025)
Background: Povidone iodine is widely used in wound healing, but it can cause irritation and cellular toxicity. Clitoria ternatea L. has the potential to contain compounds such as rutin, quercetin 3-O-rhamnoside, ternatin, and anthocyanins as natural alternatives in wound healing. In this study, the extract used contains anthocyanins.Objective: The study aimed to evaluate the effects of Clitoria ternatea L. extract cream on the expression of Interleukin-6, Epidermal Growth Factor, and re-epithelialization in Sprague Dawley rat incision wounds.Methods: An in-vivo study with a post-test only control design was conducted on five treatment groups, including a control group without wounds (healthy), povidone iodine, and Clitoria ternatea L. extract cream (5%, 10%, 15%). IL-6 and EGF were analyzed using immunohistochemistry, while re-epithelialization was assessed using hematoxylin-eosin staining.Results: Clitoria ternatea L. extract increased IL-6 and EGF expression, with the highest expression at a 10% concentration. Re-epithelialization was faster in the treatment groups compared to both the positive and negative controls.Conclusion: The 10% Clitoria ternatea L. extract cream demonstrated efficacy comparable to povidone iodine in incision wound healing.